2019
DOI: 10.1016/j.jnucmat.2019.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the stability of passivating gel layers formed on International Simple Glass

Abstract: It is known for decades that silica saturated solutions allow borosilicate glass to dissolve much slower than in deionized water. The present study assesses this assertion in the specific case of the International Simple Glass, a 6-oxide borosilicate glass of nuclear interest, which we altered between pH = 1 and 10.7 at 90 °C. Depending on the stage of reaction, aqueous silica can promote either the formation of a passivating gel layer on the glass surface or the precipitation of certain secondary phases at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…It has been well documented that glass corrosion rate in diluted solutions is enhanced by several orders of magnitude under both acidic and alkaline conditions relative to neutral conditions 22,23 . Recent studies showed that this statement is still valid when the glass corrosion reaches a steady state regime (stage II) where the solution is saturated with silica, although the rate-limiting mechanisms are likely not the same for the two regimes 24 . Therefore, the corrosion of SS in close proximity to glass could significantly enhance glass corrosion at both the anode and the cathode sites on the SS.…”
Section: Corrosion Of Soda-lime Silica Glassmentioning
confidence: 99%
“…It has been well documented that glass corrosion rate in diluted solutions is enhanced by several orders of magnitude under both acidic and alkaline conditions relative to neutral conditions 22,23 . Recent studies showed that this statement is still valid when the glass corrosion reaches a steady state regime (stage II) where the solution is saturated with silica, although the rate-limiting mechanisms are likely not the same for the two regimes 24 . Therefore, the corrosion of SS in close proximity to glass could significantly enhance glass corrosion at both the anode and the cathode sites on the SS.…”
Section: Corrosion Of Soda-lime Silica Glassmentioning
confidence: 99%
“…Depending on temperature (25-90°C) as well as solution and glass composition, corrosion rates of nuclear waste glasses can vary over 4 to 6 orders of magnitude (from a few µm/day for the initial dissolution rate measured in dilute solutions to a few nm/year for the residual rate measured in silica saturated solution). A low temperature, Si-rich solutions with pH 25°C between 9 and 10 lead to extremely low corrosion rates 7 , which are expected to translate to glass package lifetime on the order of 10 5 -10 6 years. However, despite being arguably the most important glass corrosion regime, the residual rate regime remains poorly understood and glass scientists are unable to accurately predict glass durability in the passivation regime 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…While alteration layers of ISG formed in initially dilute solutions of various pH were analyzed in this work, Fournier et al conducted a similar study using ISG in initially silica saturated solutions. 53 In their work, experiments were performed at higher S/V ratios for longer durations, but observed similar alteration behavior from pH 90°C 1 to 11. 53 The analysis performed after 7 days of alteration in this work at lower S/V is relevant to long-term glass alteration, although some specific processes can only be captured with longer reaction times such as in Fournier et al (secondary phase precipitation, alteration layer evolution with time, etc.)…”
Section: Discussionmentioning
confidence: 75%
“…53 The analysis performed after 7 days of alteration in this work at lower S/V is relevant to long-term glass alteration, although some specific processes can only be captured with longer reaction times such as in Fournier et al (secondary phase precipitation, alteration layer evolution with time, etc.) 53 .…”
Section: Discussionmentioning
confidence: 99%